Faktor-Faktor Yang Berhubungan Dengan Partisipasi Lansia Pada Kegiatan POSBINDU Di Wilayah Kerja PUSKESMAS Bintang Kabupaten Aceh Tengah Tahun 2022 - Sintia, Nazhira Arifin, Tiara Mairani (Journal of Health and Medical Science, 2022)
Posbindu for the elderly is an integrated service post for the elderly at the village/kelurahan level within the work area of each public health center. Elderly who are not active in participating in the activities of the elderly posbindu, then the health condition of the elderly is not monitored properly and it is feared that it will threaten the lives of the elderly with various kinds of diseases, both infectious and non-communicable, which are very dangerous for the body. The purpose of the study: to find out the factors related to the participation of the elderly in posbindu activities in the Working Area of the Bintang Health Center in 2022. This type of research is descriptive analytic with cross-sectional. The sampling technique in this study was simple random sampling (simple random sample. The sample in this study amounted to 87 elderly people aged ? 60 years. The study was carried out on March 20 to March 30, 2022. Data collection was done by interview using a questionnaire, then Statistical tests were carried out with the chi-square test, the data were analyzed using SPSS version 22. The results of the univariate study showed that 57.5% of early advanced age (55-64 years), the last education category was not in school at 50.6%, occupation in the household category was 41.4%, the participation of the elderly in the inactive category was 63.2%, knowledge in the category of less good 60.9%, access from home to posbindu in the unreachable category 62.1%, the role of cadres in the non-existent category 59.8%, the family role in the non-existent category 58.6%, the motivation in the non-existent category 59.8% and the type of female sex 70.1%. From the results of the bivariate statistical test, it was found that there was a knowledge relationship (p value = 0.012), access from home to posbindu (p value = 0.026), cadre role relationship (p value = 0.020), family role relationship (p value = 0.032), relationship motivation (p value = 0.020), and the relationship between sex (p value = 0.007) with the participation of the elderly in Posbindu activities in the Bintang Puskesmas Work Area, Central Aceh Regency in 2022. The conclusion of this study is that knowledge, access from home to posbindu, role of cadres, family role, motivation, and gender are factors related to elderly participation in posbindu activities in the Working Area of the Bintang Health Center, Central Aceh Regency in 2022. It is recommended that health workers can implement Posbindu for the elderly according to the mechanism for Posbindu for the elderly.